The Translation of Algerian Heritage Treasures by French Military Interpreters: A Critical Analysis of Arnaud’s Translation of Abou Ras Ennacer’s Extraordinary Travels and Pleasant Tales: ترجمة كنوز التراث الجزائري على يد المترجمين العسكريين الفرنسيين – دراسة نقدية لترجمة أرنو لكتاب «الرحلات العجيبة والأخبار الممتعة» لأبي راس الناصر - KAZI-TANI , Lynda (Maalim, 2026)
This article examines the colonial translation of Algerian heritage by French military interpreters, focusing on Arnaud’s late nineteenth-century version of Voyages Extraordinaires et Nouvelles Agréables (عجائب الأسفار ولطائف الأخبار) by Abou Ras Ennacer. It analyzes the discrepancies between the original work and its translation, highlighting the ideological biases inherent in the colonial context. The study emphasizes the tension between fidelity to the author’s stylistic and intellectual intent and the potential instrumentalization by the translator. It argues that the translation of Algeria’s cultural treasures should be entrusted to local translators, ensuring both the authenticity of the texts and respect for the historical and intellectual role of their authors.